Physical confinement promotes mesenchymal trans-differentiation of invading transformed cells in vivo - Teresa Zulueta-Coarasa; John Fadul; Marjana Ahmed; Jody Rosenblatt (iScience, 2022)
Summary: Metastasis is tightly linked with poor cancer prognosis, yet it is not clear how transformed cells become invasive carcinomas. We previously discovered that single KRasV12-transformed cells can invade directly from the epithelium by basal cell extrusion. During this process, cells de-differentiate by mechanically pinching off their epithelial determinants, but how they trans-differentiate into a migratory, mesenchymal phenotype is not known. Here, we demonstrate that basally extruded KRasV12-expressing cells become significantly deformed as they invade the zebrafish body. Decreasing the confinement that cells experience after they invade reduces the percentage of KRasV12 cells that trans-differentiate into mesenchymal cell types, while higher confinement increases this percentage. Additionally, increased confinement promotes accumulation of internal masses over time. Altogether, our results suggest that mechanical forces drive not only de-differentiation of KRasV12-transformed epithelial cells as they invade but also their re-differentiation into mesenchymal phenotypes that contribute to distant metastases.